A Study on Perception and knowledge regarding HIV/AIDS among school students and significance of educational intervention - Dhungel, BA; Chaudhary, M; Singh, S (Janaki Medical College Journal of Medical Science, 2014)
Background and objectives: HIV/AIDS is a burning crisis worldwide. Cure of HIV is not yet possible so prevention is of prime importance in control of HIV. Education plays an important role in bringing awareness. This study is planned to find the existing knowledge and significance of educational intervention. Material and Methods: This study was an experimental design in which same group of subjects (students to class 9 and 10) of selected schools in Imadol, served as control and experimental group. Participants’ perception and knowledge about various aspects of HIV/AIDS were studied by noting their agreement with a set of 65 statements (questionnaire) using a modified Likert-type scale. The data was entered in SPSS. A p value less than 0.05 were taken as statistically significant. Result: In this study, educational intervention has proved statistically significant in public school (p value 0.02). Among different sub groups total median score for knowledge about HIV/AIDS and idea about vulnerable group was also statistically significant ( p value 0.01). Conclusion: Educational intervention does play significant role in strengthening knowledge and perception regarding issues related to HIV/AIDS. DOI: http://dx.doi.org/10.3126/jmcjms.v2i1.11418 Janaki Medical College Journal of Medical Sciences (2014) Vol. 2 (1):44-51